2012
DOI: 10.1179/2045772312y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of traumatic spinal cord injury in Asia: A systematic review

Abstract: Study design: A systematic review. Background: The number of traumatic spinal cord injury (TSCI) reports grows annually, especially in China and Korea. The epidemiological characteristics of TSCI in Asia differ from those in other countries. Thus, we compiled epidemiological factors from Asia to compare with those from other countries. Method: We searched articles published in any language between January 1980 to December 2011 using the terms "spinal cord injury", "traumatic spinal cord injury", "epidemiology"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
103
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 66 publications
14
103
1
13
Order By: Relevance
“…Majority of the participants of this study had traumatic paraplegia (51.9%) and the principle cause was fall from height (45.4%) and road traffic accident (25.9%) which was found to be consistent with other global literatures [3][4][5]8,9]. 40 patients reported Bull attack to be the cause of spinal cord injury in this research which is a fairly new and interesting phenomenon which was not previously reported.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Majority of the participants of this study had traumatic paraplegia (51.9%) and the principle cause was fall from height (45.4%) and road traffic accident (25.9%) which was found to be consistent with other global literatures [3][4][5]8,9]. 40 patients reported Bull attack to be the cause of spinal cord injury in this research which is a fairly new and interesting phenomenon which was not previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…Male predominance previously reported in both local [2,3,5,14] and global [1,3,4,8,9,10] studies were also found in this research where 86.8% (n=1897) were male and 13.1% (n=287) were female. Distribution of age in this study showed more people in their 2 nd decade and 3 rd decade was vulnerable to spinal cord injury which was different from Hossain et al where the mean age was 47.44 [17] and Ulrich et al who found the mean age to be 36.1 [18].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations